FAKTOR-FAKTOR YANG MEMPENGARUHI PEMAHAMAN UMKM DALAM MENYUSUN LAPORAN KEUANGAN BERDASARKAN SAK ETAP - Rias Tuti; S, Patricia Febrina Dwijayanti (Jurnal Akuntansi Kontemporer, 2020)
The role of the MSMes (micro, small and medium enterprises) in boosting the economy and lowering unemployment in Indonesia is very large. However, sometimes the MSMes face some problems in the development of funding efforts. The cause is the unavail-ability of financial reports based on ETAP SAK can facilitate access to bank lending. The unavailability of financial re-ports based on the SAK ETAP on MSMes because of several factors, namely, the cost is relatively expensive to pay for experts in the fields of accounting, a lack of understanding of the SAK ETAP, complicated and the perception of MSMes who consider finan-cial reports not important to do. This research aims to obtain empirical evidence whether the giving of information and socialization, educational back-ground, level of education, size of enterprises and enterprises long effect on the understanding of MSMes in drawing up financial state-ments based on the SAK ETAP. Objects in the study of UMKM in Surabaya with number of respondents as much as 52 MSMes with characteristics of small and medium enterprises. Data retrieval in this study using a questionnaire which is then processed using logistic regression analysis. The results of the study prove that giving information and socialization, educational background, level of education and business size does not influence on the understanding of MSMes in drawing up financial statements based on the SAK ETAP. Only long influential usahalah significantly to the understanding of MSMes in drawing up financial state-ments based on the SAK ETAP.